Phytochemicals Screening and Effectiveness of Free Radical Inhibitors of Garlic (Allium sativum L.) Ethanol Extract from Timor Island - Priska, Melania; Peni, Natalia; Carvallo, Ludovicus (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
The purpose of the study was to determine the content of secondary metabolites and the effectiveness of garlic (Allium sativum L.) ethanol extract from Timor island which has the potential to inhibit free radicals. The method used for testing secondary metabolites is phytochemical screening using color reagents. The effectiveness of free radical inhibitors from the ethanol extract of garlic (Allium sativum L.) from Timor island was carried out in two steps are: 1.) Determination of DPPH wavelength (Î») maximum and 2.) Measurement of antioxidant activity using the DPPH method. The results showed the ethanol extract of garlic (Allium sativum L.) from Timor Island contained secondary metabolites of flavonoids, phenols, and terpenoids. The ethanol extract of garlic (Allium sativum L.) from Timor Island also has strongest effectiveness in inhibiting free radicals, with the acquisition of IC50 values <50 ppm which is equal to 9,729 ppm